Handbook of modern sensors : physics, designs, and applications - Fraden, Jacob (Woodbury, N.Y. : American Institute of Physics, 1996)
The Development of faster, more accurate, more sensitive sensors continues, with scientists creating and refining new ways for translating physical values into electronic information. This authoritative handbook takes readers to the cutting edge of sensor technology, providing an expert assessment of current research at the crossroads where the digital, analog, and physical worlds meet.
Written by one of the field's leading specialists, Handbook of Modern Sensors is the only book of its kind: a quick-access guide to the basic principles, design specifications, and uses of a number of important contemporary sensors and detectors. No other volume offers such a clearly written presentation of theoretical and practical information in such a streamlined format.
Handbook of Modern Sensors begins with the basic physical principles that form the foundations of sensor design, then explores the interfaces between sensors and peripheral processing devices. This paves the way for the book's survey of current sensors - coverage organized by the type of variable being measured (from acceleration to vibration).
While ranging across a wide variety of devices, the book emphasizes those that are less well known, whose technology is on the rise, and whose existence is making previously inaccessible measurements possible. Thoroughly revised and updated throughout, the Second Edition features new sections on acoustic waves temperature and on temperature and chemical sensors, plus a new chapter on manufacturing methods and materials.
. Handbook of Modern Sensors, with its state-of-the-art perspective, is a valuable source of information for physicists and engineering professionals. Yet its easy-going writing style, clear descriptions, and focus on the fundamentals make the book supremely accessible to students as well.
Ch. 1. Data Acquisition -- Ch. 2. Sensor Characteristics -- Ch. 3. Physical Principles of Sensing -- Ch. 4. Interface Electronic Circuits -- Ch. 5. Position, Level, and Displacement -- Ch. 6. Occupancy and Motion Detectors -- Ch. 7. Velocity and Acceleration -- Ch. 8. Force and Strain Sensors -- Ch. 9. Pressure Sensors -- Ch. 10. Flow Sensors -- Ch. 11. Acoustic Sensors -- Ch. 12. Humidity and Moisture Sensors -- Ch. 13. Light Detectors -- Ch. 14. Radiation Detectors -- Ch. 15. Electromagnetic Field Detectors -- Ch. 16. Temperature Sensors -- Ch. 17. Chemical Sensors -- Ch. 18. Sensor Technologies.
Includes bibliographical references and index.
Keywords: Detectors; Interface circuits